English idioms: An Islamic perspective - Othman, Khairiah; Abdul Malik, Faridah; Engku Ibrahim, Engku Haliza (American scientific publishers, 2017)
Many advocate that a mastery of idioms is a reflection of native speakers’ proficiency. While understanding idioms is an important part of language acquisition, a language reflects its culture. The interconnectedness between English idioms and western culture may create uneasiness on some non-native learners as the usage of some idioms may not be in-line with their value system. This article aims to highlight the presence of some English idioms which are not in line with the principles of Islam and hence, may not be appropriate for Muslims to use. The study employed a content analysis method in analysing the idioms. The findings indicate the presence of English idioms which include terms with reference to the cross and Christianity, equating men to dogs and pigs, as well as a positive image of alcohol which are incongruent with Islamic principles, hence the need for Muslims to view English idioms critically. This study has pedagogical implications for teaching English to Muslim learners. Keywords: idioms, culture, Muslims, ESL/EFL